NAHWU, ORIGIN AND ITS URGENCES IN ARABIC LEARNING - Asy'ari, M.; Idhan,; Punawan, Ahmad Sehri bin (International Journal of Psychosocial Rehabilitation, 2020)
Nahwu's study as a method focuses more on the issue of rules or conditions that apply to the position of one word in a sentence. It can also be said that Nahwu's lessons focus more on knowing how the final form of a word, i`râb or mabni. At least this kind of material is found in learning nahwu from the ibtidai level, even to universities in Indonesia until now. In this discussion will discuss the history of the emergence of nahwu science, its development, as well as figure who gave rise to the science of nahwu. The object of this nahwu science study is to focus on the last line of a word in an Arabic sentence and the changes that occur due to changes in the function of the word in the sentence, using certain signs. Nahwu's science, it was carried out by his students Abu Aswad ad- Duali even though he was not the student he directly taught but remained in the series of students because of the learning from the teacher for students and from the muri for students. Among them was Abu Bisyr Ibn Amr Ibn Uthman Ibn Qanbar, known as Imam Sibawaihiy (w.180H). he had compiled a book of nahwu with the title al-kitab which most scholars considered as the main book of nahwu (Qur'an An-nahwi), which was unequaled both before and after, and the last period in Basrah was al-Mubarrid. many nahwu experts in Basrah are inseparable from the role of al-Madrasah al-Basriyah (a special Madrasah formed to nurture the nahwu cadres in Basrah) which was founded during the time of al-Khalil Ibn Ahmad.